Pengukur Suhu Badan Otomatis untuk Masuk Ruangan Berbasis Sensor Inframerah Mlx 90614 - Arba'i Yusuf; Asni Tafrikhatin; Erman Al Hakim; Ngabdur Rojak (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2021)
The Covid-19 virus has begun to spread throughout the world, as a result, measuring human temperature has become one of the references for entering public places. Most public places have body temperature meters, as a countermeasure against the spread of the virus. The thermometer used has used infrared, but has not used a microcontroller. The purpose of this research is to make a thermometer using Arduino nano and an infrared sensor as a reader. This research method is experimental. This developed product uses the MLX90614 infrared sensor. This product uses an Arduino nano microcontroller and there is an output in the form of a 128 x 64 oled LCD. Based on the experimental results, the thermometer sold in the market with the developed thermometer has an accuracy of 99.798%.